2022
DOI: 10.1021/acs.langmuir.1c02767
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Droplet Pinning Force in the Transition from Dry to Liquid-Infused Thin Polymer Films

Abstract: The change in the pinning force during the transition from dry to oil-impregnated thin polymer films is studied for droplets of water and hexadecane. A careful variation of the oil amount in the films is performed by means of supercritical impregnation. The film thickness dependence on the oil content is measured using ellipsometry and compared to gel swelling theory estimates. Depending on the oil content, two cases of pinning force behavior have been identified. For each case, the factors that determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…48,51 It has been shown that the pinning force of the test droplets in the transition from dry to swollen fluorinated polymer matrix is well described by the de Gennes theory of diluted defects. 52 This work was inspired by the result of Zhang et al, 33 who observed a nonmonotonic change in the sliding angle with varying the number of brushes. The authors put forward a hypothesis about the relationship between film slippery properties and viscoelasticity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…48,51 It has been shown that the pinning force of the test droplets in the transition from dry to swollen fluorinated polymer matrix is well described by the de Gennes theory of diluted defects. 52 This work was inspired by the result of Zhang et al, 33 who observed a nonmonotonic change in the sliding angle with varying the number of brushes. The authors put forward a hypothesis about the relationship between film slippery properties and viscoelasticity.…”
Section: Introductionmentioning
confidence: 98%
“…Deposition from supercritical and subcritical CO 2 -based solutions expands the applicability of slippery polymer coatings to textiles, electrodes, and other substrates with complex morphology. We have recently demonstrated the possibility of using supercritical CO 2 for one-stage thin organogel SLIPS synthesis. , It has been shown that the pinning force of the test droplets in the transition from dry to swollen fluorinated polymer matrix is well described by the de Gennes theory of diluted defects …”
Section: Introductionmentioning
confidence: 99%